Employee’s “Working Obligation” for a Certain Period or Alternative Costs’ Reimbursement Resulting from Employer’s Provision of Specific Training or Financing of Education - Primož Rataj (Zbornik Znanstvenih Razprav)
The author focuses on the interplay between rights and obligations of the parties in the employment relationship stemming from provision and financing of educational or training programmes for employees. In contemporary labour law, employers wish to invest in their employees while seeking safeguards to recoup the benefits, often resulting in obliging the employees to continue working for them for a certain period or otherwise be required to reimburse (part of ) the costs incurred (hereinafter “working obligation”). Constitutional (a)symmetries can in this case be two-fold. In the ambit of EU law, it is assessed (within the framed context) to what extent is the right to education, training, and life-long learning to maintain and acquire skills that enable them to participate fully in society and manage successfully transitions in the labour market (as a social right) (in)compatible with the (economic) freedom of movement for workers. From a nation-al constitutional law perspective, boundaries between the restriction of free choice of employment (as a social freedom) and the protection of employer’s (economic) right to property are assessed. Within the EU law framework, the idea is to show, through vividly illustrated CJEU cases, that economic freedom of movement for workers is the general rule and exceptions are rarely accepted. This is important, as comparatively, practically all Member States provide for some form of a legal framework towards the existence of the “working obligation” phenomenon. The framed topic in Slovenia is regulated through more or less all pathways that can be identified comparatively, which can be observed in several specific statutes—the State Legal Exam Act, the Medical Practitioners Act, the Civil Servants Act, the Defence Act and the Slovenian Armed Forces Act (each with their own specifics), and also in some sectoral collective agreements. It cannot be overlooked that majority of these tie employees with an obligation to continue working for their employer after an education or training programme has concluded (only) in relation to its duration. In the last decade, changes in the Slovenian case-law can be observed, most importantly from judgment(s) of the Slovenian Supreme Court, which assessed contractual (and not statutory) provisions. It is clearly stressed that such contractual arrangements may be examined from a civil law perspective where the key principle of equivalence of obligations is relevant. In this sense, rights and obligations of both parties are (to be) assessed from a financial point of view, meaning that the “working obligation” should only last so long that the employer’s “investment” is recouped. Alongside dura-tion of the training, it is important to also consider the costs of such education, whether the employee has to fully or partly work while undergoing education, in whose interest the education is undertaken, etc. It is questionable to what extent are Slovenian statutory rules still in symmetry with the argumentation and reasoning provided by the Supreme Court. Furthermore, even if they were to be accepted as constitutional, it is question-able how assessment of these provisions would fare before the CJEU where the workers’ freedom of movement is the general rule and rights of others (seen as public interest) the exception that needs to be understood restrictively